2010
DOI: 10.1002/pssb.201046352
|View full text |Cite
|
Sign up to set email alerts
|

Three‐dimensional GaN for semipolar light emitters

Abstract: Selective-area epitaxy is used to form three-dimensional (3D) GaN structures providing semipolar crystal facets. On full 2-in. sapphire wafers we demonstrate the realization of excellent semipolar material quality by introducing inverse GaN pyramids. When depositing InGaN quantum wells on such a surface, the specific geometry influences thickness and composition of the films and can be nicely modeled by gas phase diffusion processes. Various investigation methods are used to confirm the drastically reduced pie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
70
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 66 publications
(77 citation statements)
references
References 57 publications
7
70
0
Order By: Relevance
“…But, as the quantization cannot exclusively explain the huge spectral shift of 1 eV along the facet, the Inincorporation has to change also. Optical simulations based on the emission energies and lifetimes from CL suggest an In-content of 20% at the ridge and below 10% at the center [13]. Additionally, high In-containing ternary QWs show statistically stronger fluctuations in indium incorporation as well as in well thickness both giving rise to strong localization of carriers in the local band profile.…”
Section: Samplesmentioning
confidence: 94%
See 2 more Smart Citations
“…But, as the quantization cannot exclusively explain the huge spectral shift of 1 eV along the facet, the Inincorporation has to change also. Optical simulations based on the emission energies and lifetimes from CL suggest an In-content of 20% at the ridge and below 10% at the center [13]. Additionally, high In-containing ternary QWs show statistically stronger fluctuations in indium incorporation as well as in well thickness both giving rise to strong localization of carriers in the local band profile.…”
Section: Samplesmentioning
confidence: 94%
“…Although the huge spontaneous and piezoelectric polarization of the wurtzite nitride system is drastically reduced on the semipolar plane, the internal electric fields still have consequences on the SQW luminescence via the QCSE reducing the recombination probability and hence increasing the carrier lifetimes for higher indium contents and thicker wells. Indeed, TEM provides a relatively thick QW of about 5 nm at the ridge which gets thinner towards the center reaching a width of less than 3 nm [13]. But, as the quantization cannot exclusively explain the huge spectral shift of 1 eV along the facet, the Inincorporation has to change also.…”
Section: Samplesmentioning
confidence: 98%
See 1 more Smart Citation
“…While vertical (non-polar) side facets can be realized, too, they are not focus of this work. A review of 3D growth can be found in [10]. For direct electrical operation of LEDs, flat sample surfaces are far more convenient and compatible with conventional processing.…”
Section: Selective Growth For Semipolar Quantum Wellsmentioning
confidence: 99%
“…Thus, it can be realized on cheap and large substrates. High crystal quality has already been achieved [10] and LEDs with semipolar QWs based on m sized 3D structures have been reported [11][12][13][14][15]. Yet, these 3D topologies require specially adapted device processing.…”
mentioning
confidence: 99%